THE KNOWLEDGE LEVEL OF FARMERS OF BIOSECURITY POST OF FOOT AND MOUTH DISEASE EPIDEMIC IN MEDAHAN VILLAGE, BLAHBATUH DISTRICT, GIANYAR REGENCY, BALI - I Made Adi Brahmantika; I Wayan Masa Tenaya; I Gusti Ayu Agung Suartini; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2024)
Foot and mouth disease (FMD) is an infectious disease caused by viruses of the genus Aphthovirus and prevention can be done by applying biosecurity principles. Biosecurity has three important components, namely isolation, traffic control and sanitation. This research aims to determine the level of knowledge of farmers regarding biosecurity after the FMD outbreak in Medahan Village, Blahbatuh District, Gianyar Regency. The design of this research was observational by interviewing 54 cattle and pig farmers conducted from November to December 2023 using a questionnaire containing 20 questions. The data obtained was then analyzed descriptively quantitatively and presented in the form of tables/diagrams. To determine the relationship between age, breeder's main occupation, education, and number of livestock with the breeder's level of knowledge, Chi-Square analysis was carried out using SPSS version 25 for Windows. The research results showed that breeders in Medahan Village had a good level of knowledge on sanitation competence, sufficient knowledge on isolation competence, and poor knowledge on traffic control competence. These results are influenced by educational factors, the farmer's main job, and the number of livestock. The conclusion of this research is that in general breeders in Medahan Village have a low level of knowledge regarding biosecurity after the FMD outbreak. A socialization program regarding biosecurity principles that is more targeted and reaches the target of FMD-vulnerable animal breeders needs to be carried out to re-emerge FMD outbreaks.